Feasibility of a new intervention addressing group-based balance and high-intensity training, physical activity, and employment in individuals with multiple sclerosis: a pilot randomized controlled trial - Ellen Christin Arntzen; Ellen Christin Arntzen; Tonje Braaten; Tonje Braaten; Hanne Kristin Fikke; Britt Normann; Britt Normann (Frontiers Media S.A., 2024)
Background and purposeImpaired sensorimotor function, reduced physical activity and unemployment are common challenges in persons with multiple sclerosis (pwMS), even when disability is low. CoreDISTparticipation is a new, multidisciplinary intervention delivered across healthcare levels systematically addressing these elements. This study primarily aimed to evaluate the feasibility of CoreDISTparticipation in terms of process, resources, management, and scientific outcomes. The secondary aim was to evaluate initial efficacy in terms of possible short-term effects compared with the usual care on barriers to employment, balance, walking, health-related quality of life (HRQoL), and physical activity.MethodsThis assessor-blinded prospective pilot randomized controlled trial included 29 pwMS [Expanded Disability Status Scale (EDSS): 0-3.5] randomly allocated to the intervention group (CoreDISTparticipation) (n = 15) or usual care (n = 14). CoreDISTparticipation consists of three phases: (1) hospital outpatient clinic: MS nurse work-focused session and physiotherapist exploring balance; (2) municipality: a digital meeting with pwMS, employer, MS nurse, and physiotherapist addressing employment and physical activity, 4 weeks indoor CoreDIST balance training (60 min × 2/week); and (3) 4 weeks outdoor CoreDIST balance training and high-intensity running/walking (60 min × 2/week). Assessments were undertaken at baseline and at weeks 6 and 11. Primary feasibility metric outcomes were the reporting of process, resources, management, and scientific outcomes. Efficacy measures included evaluation of the Multiple Sclerosis Work Difficulties Questionnaire-23 Norwegian Version (MSWDQ-23NV) and 6 Minute Walk-test as well as the Trunk Impairment Scale-modified Norwegian Version, Mini-Balance Evaluation Systems Test (Mini-BESTest), Multiple Sclerosis Walking Scale-12, Multiple Sclerosis Impact Scale-29 Norwegian Version (MSIS-29NV), ActiGraph wGT3x-BT monitors, and AccuGait Optimized force platform. The statistical analyses included repeated-measures mixed models performed in IBM SPSS Version 29.ResultsThe primary feasibility metric outcomes demonstrated the need for minor adjustments in regard to the content of the intervention and increasing the number of staff. In regard to the efficacy measures, one person attended no postintervention assessments and was excluded, leaving 28 participants (mean EDSS: 1.8, SD: 1). The mean percentage employment was 46.3 (SD: 35.6) and 65.4 (SD: 39.3) in the CoreDISTparticipation and usual care group, respectively. No between-group differences were found. MSWDQ-23NV demonstrated a within-group difference of 5.7 points from baseline to Week 11 (P = 0.004; confidence interval: 2.2-9.3). Mini-BESTest and MSIS-29NV demonstrated within-group differences. The study is registered in ClinicalTrials.gov (Identifier: NCT05057338).DiscussionThe CoreDISTparticipation intervention is feasible to support pwMS when the identified feasibility metric outcomes in regard to process, resource, management, and scientific outcome metrics are adjusted to improve feasibility. Regarding efficacy measures, no between-group differences were detected; however, within-group differences in barriers to employment, balance, and HRQoL were detected for the CoreDISTparticipation group. A larger comparative trial is needed to explore between-group differences and should accurately and precisely define usual care and address the identified limitations of this study.